SEKOLAH DASAR ALAM DI PEDALAMAN PEGUNUNGAN MERATUS LOKSADO - Hadariah Hadariah; Dila Nadya Andini (ULM Press, 2024)
Ecological disasters such as landslides and floods caused by natural exploitation in the Meratus Mountains in the form of mining and oil palm plantations should be able to foster a sense of environmental concern for the community to preserve and restore damaged natural conditions. Facilitating children in rural areas with natural schools that introduce the environment to children to develop sensitivity to the environment from an early age. The low number of schools in Loksado Sub-District is also the background to the design of a natural elementary school in the interior of the Loksado Meratus Mountains. This is very important to facilitate the education of rural communities.